Severity of COVID-19 infection in ACEI/ARB users in specialty hospitals: A retrospective cohort study. Issue 6 (June 2021) - Alrashed, Ahmed A.; Khan, Tahir M.; Alhusseini, Noara K.; Asdaq, Syed Mohammed Basheeruddin; Enani, Mushira; Alosaimi, Bandar; Alkhani, Nada M.; Mohzari, Yahya; Alghalbi, Maram M.; Alfahad, Wafa; Alanazi, Mona A.; Albujaidya, Asma S.; et al.
Abstract: Background: The uncertainty about COVID-19 outcomes in angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB) users continues with contradictory findings. This study aimed to determine the effect of ACEI/ARB use in patients with severe COVID-19. Methods: This retrospective cohort study was done in two Saudi public specialty hospitals designated as COVID-19 referral facilities. We included 354 patients with a confirmed diagnosis of COVID-19 between April and June 2020, of which 146 were ACEI/ARB users and 208 were non-ACEI/ARB users. Controlling for confounders, we conducted multivariate logistic regression and sensitivity analyses using propensity score matching (PSM) and Inverse propensity score weighting (IPSW) for high-risk patient subsets. Results: Compared to non-ACEI/ARB users, ACEI/ARB users had an eight-fold higher risk of developing critical or severe COVID-19 (OR = 8.25, 95%CI = 3.32–20.53); a nearly 7-fold higher risk of intensive care unit (ICU) admission (OR = 6.76, 95%CI = 2.88–15.89) and a nearly 5-fold higher risk of requiring noninvasive ventilation (OR = 4.77, 95%CI = 2.15–10.55). Patients with diabetes, hypertension, and/or renal disease had a five-fold higher risk of severe COVID-19 disease (OR = 5.40, 95%CI = 2.0−14.54]. These results were confirmed in the PSM and IPSW analyses. Conclusion: In general, but especially among patients with hypertension, diabetes, and/or renal disease, ACEI/ARB use is associated with a significantly higher risk of severe or critical COVID-19 disease, and ICU care.